Research on social e-commerce marketing model innovation of craft beer under digital background - WANG Chonghong, WEI Yunyi, ZHANG Yuanji (Zhongguo niangzao)
Using managers of craft beer enterprises, operators of social e-commerce platforms, and consumers of craft beer as research samples, an innovative marketing model of social e-commerce for craft beer was constructed by applying grounded theory. The results showed that the social e-commerce marketing innovation model of craft beer included four types: immersive experience and virtual community operation, gamified interaction and co-creation of social e-commerce, intelligent shopping guide and subscription social mode, and social responsibility oriented social communication. Immersive experience enhanced consumers' sense of participation and belonging to the brand through virtual technology and community activities; gamification mechanisms and co-creation activities enhanced users' emotional identification with the brand, and expanded brand influence through social communication; smart guide and subscription model and the socially responsible communication model promoted consumers' trust and continuous identification through accurate recommendation and responsible communication. Based on the above results, it was recommended that craft beer companies should utilize digital tools for market segmentation and precision marketing to improve marketing efficiency; strengthen the dissemination of brand stories and cultural connotations to attract consumers through content marketing; actively build and manage virtual communities to enhance consumers' sense of belonging to the brand; and incorporate social responsibility into their corporate strategies to enhance their brand image through environmental protection and social welfare activities.